Lagrange multipliers for the intermediate metallic regions in the computation of the potential distribution of insulator chains by FEM - Cebeci, M; Kurum, H; Akpinar, S (Hemisphere Publ Corp, 1998)
It is very important to predict the behaviour of the high voltage insulators at the operating conditions from the point of improving of the design and practical selection of the insulator type. Therefore, it is necessary to compute the potential and electric field distributions and to determine the critical regions forced much more by the electric field. In case the insulator surface is clean or the pollution film at the surface is dry, a little capacitive current flows and the solution of the problem results in a capacitive potential distribution. In the numerical computational methods of potential distribution of insulator chains, it requires to insert into the resulting equation system as boundary conditions of the intermediate metallic zones that connect two units that have the same potential at every point. In this work, the potential distribution of clean insulator chains have been computed using the Finite Element Method (FEM). The metallic zones between the units have been taken into account as equipotential surfaces by Lagrange Multipliers. The computed results were compared with experimental results obtained by using the Conducting Paper Method and good agreement was observed.